Renewing the radiopharmaceutical accuracy check service for Canadian radionuclide calibrators. (March 2016) - Galea, R.; Gameil, K.
Abstract: From 1986 to 2000, a fraction of the Canadian nuclear medicine community participated in a service offered by the National Research Council (NRC) of Canada to check the accuracy of administered doses of radiopharmaceuticals. The NRC renewed this service in recent years with a revalidation and reviving of the Secondary Standard Ionizing Radiation Chamber System (SSIRCS). The NRC conducted mock services for 99 m Tc, in varying geometries (syringes and serum vials), on two NRC commercial radionuclide calibrators, and at a nuclear medicine department in Canada. These tests showed the measured doses to be within 10% of the prepared standard but in some cases were sufficiently different from unity to warrant specific geometry factors to be derived. Highlights: NRC Canada has revived a dose calibrator service for Canadian nuclear medicine. A mock service was performed at a Canadian facility testing 99m Tc. Three geometries tested in seven radionuclide calibrators, including two at the NRC.